PENENTUAN FAKTOR KALIBRASI ACCELEROMETER MMA7260Q PADA KETIGA SUMBU - Wahyudi Wahyudi; Adhi Susanto; Sasongko P Hadi; Wahyu Widada (Departemen Teknik Elektro, Universitas Diponegoro, 2010)
The features of MMA7260Q are low cost, low current consumption, low voltage operation, high sensitivity, a 1-pole low pass filter, and g-Select which allows for the selection among 4 sensitivities. The accelerometer is an acceleration sensor that output signal in voltage/g, where g is an earth gravity. The acceleration is the rate of change of the velocity of an object and the velocity is the rate of change of the position of the same object. The position is the integration of velocity and the velocity is the integration of acceleration. If the data of the acceleration of an object is known, the data of the position can obtain by applied a double integration. This paper presents the calibration factor of three axis of accelerometers. The value of three calibration factor are not same. In general, the experiment using A1 algorithm and M2 method give the smaller of error than the other. The calibrations factor are 2.1158 for x axis, 1.6873 for y axis, and 2.1539 for z axis. The error of the distance estimation is about 3% till 4 %, so the research must be developed using the digital filter. Keywords: MMA7260Q, calibration factor, three axis